Effect of Solution Concentration, Fly Ash Ratio, and Aging Time on the Quality of Nano-Silica - Setiawati, Mira; Saggaff, Anis; Saloma; Ngian, Shek Poi (Science and Technology Indonesia, 2025)
Fly ash, a byproduct of coal combustion, has gained significant attention due to its high silica content, and this silica-rich waste can be effectively converted into nano-silica. Factors such as the molarity of the solution, liquid-to-solid ratio, and the aging time play an essential role in determining the characteristics of silica nano produced, including particle size, morphology, and purity. This research aimed to determine the optimal conditions of solution molarity and the liquid-to-solid ratio to produce high-purity nano silica, examine the effect of aging time on the morphology and size of silica nanoparticles, and evaluating the effectiveness of the sol-gel method in producing nano-silica. This research uses nitric acid (HNO3 3 M) as the solution because it has not been widely explored and is more effective than other acidic solutions. In addition, the liquid-to-solid ratio varied from 1:5, 1:10, and 1:15, and combined with an aging time of 9 and 12 days, this study became the focus. The sample tested included XRD, XRF, FTIR, and SEM to confirm the nano-silica characteristics. It shows XRD is in the range of 2θ of about 20-22◦, which indicates the presence of amorphous silica, and FTIR shows results that support XRD data. SiO2 composition ranges from 97.47% to 98.57%, a very high amount of pure silica. It may concluded that silica nanoparticles have a particle size that varies from 151.2 nm to 295.4 nm, with a smooth morphology and relatively well distributed.